Information interchange services for electronic health record databases. (1st January 2012) - Sachdeva, Shelly; Madaan, Aastha; Chu, Wanming
Healthcare information is complex and distributed in nature. Patient care and a health condition commonly require collaboration between several clinicians. Such an integration of information is important to retrieve patient history, for knowledge sharing and to formulate queries. Large scale adoption of electronic healthcare applications requires semantic interoperability because patients have become mobile, treatment and healthcare providers have increased, and also, have become more specialised. Similar to the web, information retrieval is key feature of these end-user systems. The paper analyses the role of semantic interoperability in various cross-organisational business processes in healthcare domain. The system modelling approach has been analysed with a view of supporting system-to-system and user-system interactions. The paper presents a comparison of the existing information and querying methods and studies their applicability to the dual-level electronic health records (EHRs) systems. It further discusses the best approach to build a user-friendly querying interface for these systems.